RADIOCTIVE PATHWAY: A LUDIC-PEDAGOGICAL RESOURCE FOR UNDERSTANDING CONCEPT AND APPLICATIONS OF RADIOPHARMACEUTICALS (REMUNOM, 2025)
The study of radiation in Pharmacy courses is often presented in an abstract way and disconnected from professional practice, which hinders learning and reduces students’ interest. In this context, the present study suggests the use of an alternative didactic resource: a board game called Radioactive Path, created to address essential concepts and applications of radiopharmaceuticals. The game was designed using simple materials and based on participatory methodologies, aiming to promote interaction, critical thinking, and collaboration among students. This approach connects Physics theory with pharmaceutical practice while facilitating content comprehension through an interactive and engaging experience. The activity aims to make learning more relevant, reinforcing the understanding of the role of radiopharmaceuticals in healthcare.